Correlation of clinical parameters with computed tomography findings in patients with traumatic head injury in emergency services of Tribhuvan University Teaching Hospital - Jaiswal, Dhiraj Prasad; Acharya, Ramesh Prasad; Neupane, Ram Prasad (Journal of General Practice and Emergency Medicine of Nepal, 2024)
Introduction: Traumatic head injury (TBI) is a common presentation in the emergency services. Non-contrast computed tomography (NCCT) scan is the most commonly used tool for evaluation of these cases. However, its use is not justifiable when done without proper indication. There are certain Red flag signs (clinical predictors) of traumatic brain injury. A proper history and physical examination is needed to distinguish the presence of red flag signs and order a head CT if needed. The objective of this study is to find out the most predictable clinical parameters in patients with traumatic head injury where CT scan of head can play a deciding role in management. Method: An observational cross-sectional study done in 106 individuals presented to emergency with TBI and underwent head NCCT for diagnosis at Tribhuvan university teaching hospital. The duration of study was 6 months. Presence or absence of red flag signs were determined after detailed history taking and physical examination. The association of head CT positivity with presence of red flag signs was studied by bivariate analysis using the chi-square test. Result: Male were 79 (74.5%) and female were 27 (25.5%) in number with male to female ratio of 3:1. Most of the patients triaged to green area (50.9%). 66% had sustained injury to head as a result of fall injury while 26.4% has RTA. 95 (89.6%) had mild head injury and 11 (10.4%) had moderate head injury following the accident. 49 (46.2%) had red flag sign for ordering a CT scan. 25(23.58%) were positive for intracranial findings. Fracture of skull bone was found as most common CT finding in 16(15.10%) followed by sub arachnoid hemorrhage (SAH) 5(4.71%) and extra dural hematoma (EDH) 4(3.78). Conclusion: Patients with any of the red flag signs needs immediate NCCT scan of head in case of traumatic head injury.